Assessment of the ecological and tourism potential of Kharkiv region under wartime safety and environmental risks - Sysoieva, S. I. (Man and Environment. Issues of Neoecology, 2026)
Purpose. To assess the ecological and tourism potential of Kharkiv Oblast using the current administrative framework, updated data on the nature reserve fund, and wartime safety and environmental restrictions.Methods. The research applies analysis of official environmental and regulatory sources, cartographic generalization, normalized scoring, expert ranking, territorial clustering and SWOT analysis.Results. Kharkiv Oblast has considerable potential for ecological, educational, scientific and recreational tourism due to the combination of forest-steppe and steppe ecosystems, river valleys, forests, wetlands and dendrological objects. The integrated assessment combines four components: natural and ecological potential, tourism infrastructure, transport and information accessibility, and safety accessibility. Five priority ecotourism clusters were identified: Homilshany-Siverskyi Donets, Slobozhanskyi-Krasnokutsk dendrological and nature conservation, Pechenihy-Staryi Saltiv, Kupiansk-Dvorichna-Borova and Kharkiv suburban forest-park cluster. The highest effectively realized potential is recorded for the Kharkiv suburban and Homilshany-Siverskyi Donets clusters, while the Kupiansk-Dvorichna-Borova cluster retains very high natural value but has critically low safety accessibility under current wartime conditions.Conclusions. The future development of ecotourism in Kharkiv Oblast depends on environmental rehabilitation, demining, infrastructure restoration, digital visitor information and integration of territorial communities into a post-war sustainable nature management model.